{Anionically induced formation of anomeric spironucleosides from 1 '-C-cyano-2 '-deoxyuridine} - Chatgilialoglu, C; Ferreri, C; Gimisis, T. (Tetrahedron Lett., 1999)
The reaction of the 1'-C-cyano-2'-deoxyuridine derivative 1 with organolithium reagents can be favorably tuned to give a new class of anomeric spironucleosides. (C) 1999 Elsevier Science Ltd. All rights reserved.